Method for detection of the antimicrobial activity of the recombinantial peptide PEP-H - Huan, Le Quang (Academia Journal of Biology, 2015)
The gene encoding the recombinant peptide has been synthesized by chemical method and it was sucessfully expressed in E. coli. The new method was developed for detection of the antimicrobial activities of the pure recombinant peptide which after has been purified on affinity chromatography and cleaved by the factor Xa.